Distribution of varicella zoster virus and herpes simplex virus in disseminated fatal infections. - Nikkels, A F (1996)
AIMS: To study the cutaneous and visceral distribution of herpes simplex virus (HSV) and varicella zoster virus (VZV) in fatal infections. METHODS: Standard histology, immunohistochemistry (monoclonal antibodies VL8 and VL2 and polyclonal antibody IE63 directed against VZV; monoclonal antibodies IBD4 and HH2 and polyclonal antibodies directed against HSVI and HSVII) and in situ hybridisation (anti-HSV and anti-VZV probes) were applied to formalin fixed, paraffin wax sections. RESULTS: On histological examination, Herpesviridae infection was evident in various organs including the lungs, liver and skin. In addition, immunohistochemistry and in situ hybridisation revealed the presence of HSV and VZV antigens and nucleic acids in several cell types and tissues showing no cytopathological alterations suggestive of Herpesviridae infection. The organs with histological evidence of infection also contained VZV or HSV antigens and their genes. CONCLUSIONS: These findings suggest that organ failure in disseminated VZV and HSV infections is primarily caused by HSV or VZV induced cell damage and lysis. They also indicate that immunohistochemistry and in situ hybridisation can provide an accurate, type-specific diagnosis on formalin fixed, paraffin wax embedded tissue even when classic histological and cytological characteristics are lacking.